Etika Berhias Perspektif Tafsir Al-Munir: Sebuah Kajian Sosiologis - Muhamad Yoga Firdaus (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the ethics of decorated with the Tafsir Al-Munir perspective. This research method is qualitative through literature study with a sociological approach. The results and discussion of this research include the understanding of ethics, the meaning of the Tafsir Al-Munir, and the ethics decorated with the perspective of Tafsir Al-Munir on sociological analysis. This research concludes that decorating is a necessity of human life that must be equipped with ethics. The ethics inherent in decorative activities can give rise to good views from the surrounding environment to create collective goodness in the sphere of social life. This study recommends that further research be carried out related to ethics and decoration based on other interpretive perspectives.